miR-1458 is inhibited by low concentrations of Vitamin B6 and targets TBX6 to promote the formation of spermatogonial stem cells in Rugao Yellow Chicken - Qingqing Geng; Cai Hu; Ziduo Zhao; Zhe Wang; Fufu Cheng; Jing Chen; Qisheng Zuo; Yani Zhang (Poultry Science)
Spermatogonial stem cells (SSCs) have vast application prospects in livestock and poultry production, genetic engineering, and medical research. However, the scarcity of SSCs and the complexity of their development limit the elucidation and verification of the mechanism of SSCs in vitro. Although miRNAs have been identified as critical players in germ cell development, upstream regulatory mechanisms by which miRNAs regulate SSCs formation are rarely reported. In this study, miR-1458, which was differentially expressed during SSCs formation, was selected by transcriptomic sequencing. We found that miR-1458, inhibited in an in vitro SSCs induction model,significantly upregulated the expression of germline marker genes (Cvh and integrin β1). Further analysis using Immunofluorescence and Flow Cytometry confirmed that miR-1458 inhibition promotes the formation of spermatogonial stem-like cells (SSCLCs). Immunohistochemical significantly increased the number of SSCs in the testis in vivo. However, significant upregulation of miR-1458 showed opposite results. High-throughput sequencing results showed that miR-1458 interacted with TBX6, one of the target genes of miR-1458, involved in affecting cell differentiation, and dual-luciferase reporter vectors confirmed the targeting relationship between the two. TBX6 overexpression and knockdown in vitro and in vivo have validated its function in SSCs formation. We found that overexpression of TBX6 promoted SSCs formation. Additionally, we identified Vitamin B6, a key metabolite affecting SSCs formation, as an upstream regulator of miR-1458 expression. The results showed that low concentrations of Vitamin B6 led to low expression of miR-1458 by decreasing histone demethylation levels. Overall, our findings suggest that miR-1458 is involved in SSCs formation, which is inhibited by low concentrations of Vitamin B6 and subsequently regulates the formation of SSCs by targeting TBX6, an essential gene involved in embryonic stem cell differentiation. Our study demonstrates the critical role of the Vitamin B6-miR-1458-TBX6 regulatory axis in spermatogonial stem cell formation in Rugao Yellow Chicken, providing new insights into the regulatory mechanisms by which miRNAs affect SSCs formation. It should be noted that most of the germline findings related to miRNAs were obtained by in vitro studies, and in vivo studies are needed to validate our results for clinical applications.